OC-055 'ibdpassport': evaluating the quality of an internet-based travel resource for inflammatory bowel disease. (22nd June 2015) - Greveson, K; Hamilton, M; Murray, CD
Abstract : Introduction: Travellers' with Inflammatory bowel disease (IBD) are at greater risk of travel-related morbidity with European guidelines recommending expert consultation prior to travel. 1 Previous research into travel and IBD found travel consultations and patient travel preparation and knowledge to be deficient. 2, 3 As a result we developed a dedicated, evidence-based non-profit IBD travel advice website (www.ibdpassport.com ) to enhance informed, safe travel. Here we present formal evaluation of this website. Method: A link to the website, along with a structured web-based survey was sent to a sample of 15 UK IBD patients, clinical nurse specialists and Gastroenterologists respectively. The survey contained demographic questions and asked respondents to rate the content, functionality and credibility of the website using a series of parameters including a 5-point Global Quality Score and Integrity Score. 4 Readability statistics were graded on a 100 word sample of text from each page on the website using the Flesch Reading Ease and Flesch-Kincaid Grade level scores. Results: A total of 33 individuals responded (73% response rate; 11, 33% Patient; 10, 30% Nurse; 12, 36% Gastroenterologist. The mean Global Quality score was 4.5 out of a possible 5 (Range 3–5). The Flesch-Kincaid Grade level score was US school grade 10.9 (range 7.2–17.1) and median Flesch Reading Ease score 50.5 out of a possible 100 (Range 22.4–65.1). The integrity score was 4.0 out of 6. The majority of respondents strongly agreed the website was an accurate source of travel information for IBD (60%), used appropriate citations (67%), and was easy to navigate (70%). 26/33 (79%) felt the website improved their knowledge of travel-related issues in IBD. All respondents would recommend the site to peers. Conclusion: IBD Passport is the first internet-based travel resource created for both patients and professionals to provide IBD-specific travel information. Our findings demonstrate that patients and healthcare professionals consider IBD Passport to be an excellent quality, evidence-based resource. The readability statistics are favourable when compared to results from other studies examining website quality. Disclosure of interest: None Declared. References: Rahier JF, et al . J Crohns Colitis 2014;8:443–468 Soonawala D, et al . Inflamm Bowel Dis. 2012;18(11):2079–85 Greveson, et alet al. A recent flare of disease does not prohibit travel: early results of a single centre study in inflammatory bowel disease and travel digestive diseases week, 2014, abstract ID:Su1095 Bernard A, Langille M, Hughes S, et al . A systematic review of patient inflammatory bowel disease information resources on the world Wide Web. Am J Gastroenterol. 2007;102:2070–2077